Sulforaphane diminishes moonlighting of pyruvate kinase M2 and interleukin 1β expression in M1 (LPS) macrophages - Bahiraii, Sheyda; Brenner, Martin; Yan, Fangfang; Weckwerth, Wolfram; Heiss, Elke H. (Frontiers in Immunology, 2022)
Murine macrophages activated by the Toll-like receptor 4 agonist lipopolysaccharide (LPS) polarize to the M1 type by inducing proinflammatory marker proteins and changing their energy metabolism to increased aerobic glycolysis and reduced respiration. We here show that the aliphatic isothiocyanate sulforaphane (Sfn) diminishes M1 marker expression (IL-1β, IL-6, TNF-α, iNOS, NO, and ROS) and leads to highly energetic cells characterized by both high glycolytic and high respiratory activity as assessed by extracellular flux analysis. Focusing on a potential connection between high glycolytic activity and low IL-1β expression in M1 (LPS/Sfn) macrophages, we reveal that Sfn impedes the moonlighting function of pyruvate kinase M2 (PKM2) in M1 macrophages. Sfn limits mono/dimerization and nuclear residence of PKM2 accompanied by reduced HIF-1α levels, Stat3 phosphorylation at tyrosine 705, and IL-1β expression while preserving high levels of cytosolic PKM2 tetramer with high glycolytic enzyme activity. Sfn prevents glutathionylation of PKM2 in LPS-stimulated macrophages which may account for the reduced loss of PKM2 tetramer. Overall, we uncover PKM2 as a novel affected hub within the anti-inflammatory activity profile of Sfn.